Faktor-Faktor yang Mempengaruhi Perilaku Keselamatan Kerja : Kajian Fenomenologi pada Petugas Pemadam Kebakaran di Kota Jambi Tahun 2024 - Silvania Silvania; Herwansyah Herwansyah; Ismi Nurwaqiah Ibnu; Willia Novita Eka Rini; Budi Aswin (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Occupational Safety and Health (OSH) is crucial for creating safe and healthy working environments. Firefighters face significant risks in their line of duty. This research aims to identify the factors influencing work safety behavior among firefighters in Jambi City. This study employs a qualitative approach with a phenomenological design. Data was collected through in-depth interviews, observations, and document analysis. Research informants included firefighters with various roles and levels, encompassing field officers, OSH personnel, and the division head. The research examines the influence of human factors (knowledge), work environment factors (personal protective equipment/PPE, training, the role of OSH, and reward systems), and OSH indicators on work safety behavior. The findings indicate that the OSH knowledge of firefighters in Jambi City is considered adequate, with alignment between established OSH standards and the officers' perceptions. PPE is acknowledged as important, but budgetary constraints affect the availability of more specific PPE. OSH training is deemed essential for enhancing officers' knowledge and awareness. The role of OSH within the organization is seen as important for creating a safe work environment, although there are expectations for improved understanding and implementation of OSH in the field. The reward system is perceived as inconsistent. OSH indicators, such as regulations and SOPs, are considered effective guidelines for task execution. Work safety behavior among firefighters in Jambi City is influenced by a complex interplay of human factors, work environment factors, and the OSH system. Adequate OSH knowledge and effective implementation of OSH indicators form a critical foundation. However, improvements in areas such as PPE provision, consistency of the reward system, and enhanced understanding and comprehensive implementation of OSH are necessary to strengthen the safety culture and reduce the risk of workplace accidents.